Solution‐Grown Serpentine Silver Nanofiber Meshes for Stretchable Transparent Conductors. (17th September 2018) - Li, Peng; Zhang, Wei; Ma, Jiangang; Wang, Xiao; Xu, Haiyang; Cong, Lujia; Liu, Yichun
Abstract: Metal fiber nanomeshes, fabricated by depositing metals on the electrospun nanofiber templates, have come into the spotlight as promising stretchable transparent conductors. However, most currently stretchable metal fibers are produced via expensive vacuum deposition methods. This work reports a low‐cost approach to prepare transparent, conducting, and serpentine silver nanofiber mesh elastomers (SNME). The key of forming SNME is buckling the electrospun polymer nanofiber templates into wavy structure and subsequently electrolessly depositing silver on the templates. Optoelectronic performance of the SNME is elaborately optimized by tuning the number of Ag nanoseeds and the electroless deposition time. The resulting SNME exhibit a high visible light transmittance of 81%, a low sheet resistance of 9.2 Ω sq −1, and an excellent stretchability with 2.4‐times of resistance increases after repeated stretching to 70% for 1000 cycles. In situ observations indicate that the SNME are capable of straightening and rearranging to adapt to the tensile deformation. Its application potential as an ideal platform for fabricating intelligent interfaces is demonstrated by using the SNME as a wearable resistance sensor which can monitor finger joint motions. Abstract : In‐plane sinusoidal polymer nanofiber mesh templates with microwavelength are fabricated by transferring the flexible electrospun polymer nanofiber meshes to the prestrained substrates. Electroless deposition of silver on the templates results in serpentine silver nanofibers which are capable of straightening and rearranging to adapt to the tensile deformation based on the in situ observation of morphology evolution under stretching.